1988
DOI: 10.1042/bj2550795
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of the enzymes that dephosphorylate myo-inositol polyphosphates in human platelets

Abstract: The phosphatase-induced hydrolysis of [3H]inositol 1,4-bisphosphate [Ins(1,4)P2)] and [3H]inositol 1,4,5-trisphosphate [Ins(1,4,5)P3] was studied in platelet subcellular fractions. The activity that hydrolyses Ins(1,4)P2 is cytosolic, whereas the activity that hydrolyses Ins(1,4,5)P3 is present in both particulate and cytosolic fractions. The cytosolic Ins(1,4)P2 phosphatase hydrolyses the 1-phosphate of Ins(1,4)P2, whereas the cytosolic and membrane-bound Ins(1,4,5)P3 phosphatases hydrolyse the 5-phosphate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…6). A similar observation has been reported (15,21) on the decrease of ADP-ribosylation of the membrane-bound substrate of cholera toxin after 24 hr of treatment with iloprost. The cholera toxin-induced ADP-ribosylation of the cytosolic 44-kDa peptide was also decreased by pretreatment with iloprost, and this change, observed at 20 min, was more evident at 1 hr (Fig.…”
Section: Resultssupporting
confidence: 66%
“…6). A similar observation has been reported (15,21) on the decrease of ADP-ribosylation of the membrane-bound substrate of cholera toxin after 24 hr of treatment with iloprost. The cholera toxin-induced ADP-ribosylation of the cytosolic 44-kDa peptide was also decreased by pretreatment with iloprost, and this change, observed at 20 min, was more evident at 1 hr (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Antiserum A-572 recognizes the peptide Lys-Gln-LeuGln-Lys-Asp-Lys-Gln-Val-Tyr-Arg-Ala-Thr-His-Arg, which corresponds to residues 28-42 in the amino-terminal region of Gs,. In previous studies using immunoblot techniques, we showed that when platelets were incubated with iloprost under conditions in which cholera toxin-induced ADPribosylation was decreased, there was no loss of Gs, from the membrane (6). We now show that a 23-kDa peptide that is recognized by antiserum 584, but not by antiserum A-572, is lost from the membrane during treatment with iloprost and is recovered in the platelet cytosol.…”
mentioning
confidence: 62%
“…Another possibility, not addressed in this study, is that protein kinase C may be activated differently by the three agonists and that this determines the direction of the metabolism of 145IP3. In some cell types 145IP35' phosphatase has been shown to be localized at the cytoplasmic membrane (Molina et al 1988) and sensitive to phosphorylation by protein kinase C (Connolly et al 1987). However, this is not a universal finding (Biden et al 1988).…”
Section: Discussionmentioning
confidence: 98%